Associations of Il-1 Family-Related Polymorphisms With Gastric Cancer Risk and the Role of Mir-197 In Il-1f5 Expression. Issue 47 (November 2015) - Chen, Xiaolin; Xu, Yajuan; Cao, Xiaoqin; Chen, Yi; Jiang, Jicheng; Wang, Kaijuan
Abstract : Abstract: To explore whether the roles of IL-1 family single nucleotide polymorphisms (SNPs) of the microRNA binding sites (miR-SNPs) in the 3′ untranslated region (3′-UTR) of their target genes in the progression of gastric cancer (GC) and verify the relationship between miR-197 with chronic inflammatory gene-IL1-F5 by microRNA target prediction, a case-control study which consisted of 500 cases and 500 frequency-matched healthy controls was conducted. Single nucleotide polymorphisms were analyzed by polymerase chain reaction–restriction fragment length polymorphism (PCR-RFLP) or allele-specific PCR (AS-PCR). Association between SNPs and GC risk was evaluated by adjusted odds ratios (ORs) and 95% confidence intervals (CIs) in unconditional logistic regression analyses. Quantitative real-time (qRT) PCR assay and Western Blot analyses were performed to analyze the miR-197 expression and the IL1-F5 expression. The variant homozygote and heterozygote genotype of rs9005 in IL-1RN were significantly associated with increased risks of GC (ORadjusted [95%CI]: 1.71[1.04–2.81] and ORadjusted [95%CI]: 1.36 [1.04–1.78]). Compared with the wild heterozygote genotype, the variant heterozygote genotype of rs2472188 and rs2515401 in IL-1F5 polymorphisms were significantly associated with increased GC risks (ORadjusted [95%CI]: 1.51[1.15–1.99] and ORadjusted [95%CI]: 1.36[1.04–1.76]), but no significant differences existed in other 7 IL-1 family SNPs (rs2856836 in IL-1A, rs3732131 in IL-1R1, rs1135354 and rs3771157 in IL-18RA, rs3180235, rs957201 and rs2515402 in IL-1F5) with GC. The recombinant plasmid-pGenesil-1-miR-197 could upregulate the expression of miR-197 and downregulate the expression of IL-1F5 in human gastric cancer cell lines SGC-7901 and BGC-823 cells after transfection, and the miR-197 inhibitor could facilitate the expression of IL1-F5 after transfecting the same cell lines. These results suggested that SNPs in the IL-1 family genes play important roles in the development of GC and the IL-1F5 might be the target gene of miR-197, and miR-197 might negatively regulate its expression.